2020
DOI: 10.1021/acsomega.0c03003
|View full text |Cite
|
Sign up to set email alerts
|

Effect and Mechanism of Aluminum(III) for Guaiacol–Glyoxylic Acid Condensation Reaction in Vanillin Production

Abstract: 3-methoxy-4-hydroxymandelic acid (VMA) was the critical intermediate for the synthesis of vanillin by the glyoxylic acid method. Meanwhile, a valuable byproduct (2-hydroxy-3-methoxy-mandelic acid, o -VMA) was obtained during the reaction. Al 3+ was found to be a helpful catalyst in increasing the selectivity for VMA and o -VMA. In the presence of Al 3+ , the selectivity for VMA and o -VMA increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Although there are many types of Al ions in zeolites (EXFAl, A l3+ with IV, V, and VI coordination, Al 2 O 3 species), the unsaturated Al V ions having Lewis and Brønsted-type acidity , are especially prone to serve as anchor sites for metal NPs. ,,, In fact, the enhancement of metal dispersion observed for Ir–Pt/USY and Pt/USY catalysts by HRTEM could be explained by taking into account the stabilization of the metal particles by the unsaturated Al V ions . In this regard, Newman et al proposed that the main factor influencing the HYD reaction pathway is the ability of the support to stabilize small particles, and higher dispersion could be archived by using supports with higher specific area …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are many types of Al ions in zeolites (EXFAl, A l3+ with IV, V, and VI coordination, Al 2 O 3 species), the unsaturated Al V ions having Lewis and Brønsted-type acidity , are especially prone to serve as anchor sites for metal NPs. ,,, In fact, the enhancement of metal dispersion observed for Ir–Pt/USY and Pt/USY catalysts by HRTEM could be explained by taking into account the stabilization of the metal particles by the unsaturated Al V ions . In this regard, Newman et al proposed that the main factor influencing the HYD reaction pathway is the ability of the support to stabilize small particles, and higher dispersion could be archived by using supports with higher specific area …”
Section: Resultsmentioning
confidence: 99%
“…Regarding the specific properties of supports, there is evidence that noble metals supported on materials possessing a large number of pentacoordinated Al 3+ unsaturated sites (Al V : intermediate species between Al IV and Al VI ) showed increased activity in acid-catalyzed biomass conversion, sugar conversion, alcohol dehydration, and hydrogenation of aromatic ketones. In this sense, the recent finding suggests that selectivity to deoxygenated products depends on the oxophilicity of the supports , and metals . On the basis of the literature reports, the role of pentacoordinated Al V species is diverse.…”
Section: Introductionmentioning
confidence: 99%
“…It can be observed that most of the coordination centers were heavy metals leading to the limitation of their application. [36][37][38] Since 2014, Ca 2+ was used as the coordination center to prepare calcium phenolate complexes with guaiacol and its derivatives as ligands. 39 The essence of this method was to use calcium hydroxide solution to react with guaiacol or its derivatives to produce a coordination compound with a molar ratio of calcium to guaiacol of 1:4.…”
Section: Introductionmentioning
confidence: 99%
“…Guaiacol is also known as o-hydroxyanisole or o-methoxyphenol. As an important fine chemical raw material and intermediate [1][2][3], guaiacol and its derivatives are widely used in medicine [4,5], agricultural chemic [6,7], and spices [8], especially in synthesis of vanillin [9][10][11][12]. Traditionally, guaiacol is produced mainly by methylation of catechol with halogenated alkanes (CH 3 I, CH 3 CH 2 Br), (CH 3 ) 2 SO 4 , or dimethyl carbonate (DMC) in the presence of sodium hydroxide by homogeneous reaction [13][14][15].…”
Section: Introductionmentioning
confidence: 99%